Design of WZFT Mountain Rig in Mining Industry. Issue 1 (February 2021) - Liu, Ruijun; Wang, Guigen; Li, Yong; Fu, Yanlong; Huang, Guanglong; Ding, Xiaowu
Abstract: With the development of China's mining industry, in order to promote China's mineral exploration to the deep to meet the new round of industry demand, mining enterprises on mining machinery and equipment demand is increasingly high, especially drilling, field mining equipment; Improve mining machinery equipment level and efficiency of artificial intelligence is necessary, and can eliminate the safety hidden trouble, the comprehensive implementation of related equipment localization, an urgent need to study to design new functional drill, solution to meet the construction efficiency, reduce the risk of construction personnel safety, reducing the project cost and reduce soil and water loss protect the environment. The mine machinery equipment WZFT designed in this paper is specialized in drilling equipment used for blasting in various mines and drilling holes, and it is produced by Jiangxi Dongrui Machinery Co., LTD., and it is proposed to develop drilling machine in the direction of intelligentization and unmanned in the future.